Experimental investigation of grid storage modes effect on aging of LiFePO4 battery modules - Jianhong Xu; Haozhan Li; Sicong Hua; Hao Wang (Frontiers in Energy Research)
IntroductionTo investigate the degradation behavior of energy storage batteries during grid services, we conducted a cyclic aging test on LiFePO4 battery modules.MethodsIncorporating variables such as grid duty, temperature and depth of discharge, we analyzed the capacity degradation and operational patterns in different grid- storage interaction modes by examining aspects of capacity retention, discharge quantity, incremental capacity, and differential voltage.ResultsOur findings indicate that battery degradation is higher during peak shaving compared to frequency regulation. Heat and deep charging and discharging modes accelerates battery aging.DiscussionThe primary source of performance degradation in LiFePO4 batteries is Li loss.